2016
DOI: 10.1177/0145721716666678
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions About Prediabetes and Preferences for Diabetes Prevention

Abstract: Purpose The purpose of this study was to explore how adults with prediabetes perceive their risk of developing diabetes and examine their preferences for evidence-based treatment options to prevent diabetes. Methods A qualitative study was conducted in 2 large Midwest primary care practices, involving in-depth semistructured interviews with 35 adult patients with prediabetes. Results This ethnically diverse (77% nonwhite) sample of middle-aged primary care patients exhibited multiple diabetes risk factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 58 publications
3
50
1
1
Order By: Relevance
“…Participants were concerned about progressing to T2D, experiencing physical ailments associated with T2D, and exacerbating current health conditions. These findings are consistent with past research where physical concerns (Eborall et al, ), uncertainty about seriousness of the diagnosis (O'Brien et al, ; Troughton et al, ) and implications for current health problems (Peel, Parry, Douglas, & Lawton, ) have been documented. These concerns may be fuelled by uncertainty around what a prediabetes diagnosis actually means and poor communication about the diagnosis by healthcare providers (O'Brien et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Participants were concerned about progressing to T2D, experiencing physical ailments associated with T2D, and exacerbating current health conditions. These findings are consistent with past research where physical concerns (Eborall et al, ), uncertainty about seriousness of the diagnosis (O'Brien et al, ; Troughton et al, ) and implications for current health problems (Peel, Parry, Douglas, & Lawton, ) have been documented. These concerns may be fuelled by uncertainty around what a prediabetes diagnosis actually means and poor communication about the diagnosis by healthcare providers (O'Brien et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…First, healthcare professionals should be aware of the negative reactions people have upon learning about their prediabetes diagnosis and take steps to reduce these reactions. Healthcare professionals could offer patients with prediabetes a clear explanation of what prediabetes is, the health implications, the likelihood that they will develop T2D, and the risk‐reducing efficacy of lifestyle changes (O'Brien et al, ). This clear, unambiguous communication about prediabetes may mitigate distress associated with uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16,17] A study stated that the patients' perception can be influenced by their pre-service expectations of the service provider [18] that is the patients' actual knowledge of the roles and responsibilities of CNCs in this study. Another study reported that patients' perceptions of disease risks and development influenced their attitude towards treatment preferences, [19] and that an effective communication about prognosis is a prerequisite to define goals of care, making treatment decisions, and planning for the future. [20] This clearly indicates how nourishing the knowledge of cancer patients and enhancing their perception can influence their attitude to communicate such needs to CNCs.…”
Section: Discussionmentioning
confidence: 99%